The role of the community in the implementation of one roof school - Wiwik Wijayanti (Jurnal Prima Edukasia, 2020)
This study aims to describe the role of the community in the implementation of a one-roof school. To discover the role of the community, a multisite qualitative approach was employed by using the constant comparative type in order to explore data in depth. The data validity was obtained by testing the credibility, transferability, dependability, and confirmability. Then the data were analyzed using the comparative constant technique. The results of this study indicate that all policies and decisions made were joint policies and decisions. These were formulated to achieve mutual success through a mechanism known as the conception of total football by emphasizing the synergistic mobilization of forces that lead to one goal, which was improving the quality and suitability of education with the community development.